Graphene oxide and carbon dots as broad-spectrum antimicrobial agents – a minireview. Issue 1 (13th September 2018) - Anand, Anisha; Unnikrishnan, Binesh; Wei, Shih-Chun; Chou, C. Perry; Zhang, Li-Zhi; Huang, Chih-Ching
Abstract : Complex antibacterial mechanisms of graphene oxide and carbon dots. Abstract : Due to the increasing global population, growing contamination of water and air, and wide spread of infectious diseases, antibiotics are extensively used as a major antibacterial drug. However, many microbes have developed resistance to antibiotics through mutation over time. As an alternative to antibiotics, antimicrobial nanomaterials have attracted great attention due to their advantageous properties and unique mechanisms of action toward microbes. They inhibit bacterial growth and destroy cells through complex mechanisms, making it difficult for bacteria to develop drug resistance, though some health concerns related to biocompatibility remain for practical applications. Among various antibacterial nanomaterials, carbon-based materials, especially graphene oxide (GO) and carbon dots (C-Dots), are promising candidates due to the ease of production and functionalization, high dispersibility in aqueous media, and promising biocompatibility. The antibacterial properties of these nanomaterials can be easily adjusted by surface modification. They are promising materials for future applications against multidrug-resistant bacteria based on their strong capacity in disruption of microbial membranes. Though many studies have reported excellent antibacterial activity of carbon nanomaterials, their impact on the environment and living organisms is of concern due to the accumulatory and cytotoxic effects. In this review, we discuss antimicrobial applications of the functional carbon nanomaterials (GO and C-Dots), their antibacterial mechanisms, factors affecting antibacterial activity, and concerns regarding cytotoxicity.